Evaluation of the Supervisor Supervision Program in the Performance Quality of Madrasah Principals at MTsN 2 South Bengkulu - Dali, Zulkarnain; Janah, Wardatul; Aprilia, Ermi (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: The supervisory program for overseeing the performance of madrasah principals still appears to be challenging; the program does not yet seem fully structured, sustainable, or well-aligned with stakeholders. The purpose of this study is to evaluate the supervisors’ supervision program in improving the quality of madrasah principals’ performance at MTsN 2 South Bengkulu. This research uses a qualitative descriptive method with the CIPP evaluation model approach (Context, Input, Process, Product). The research subjects include madrasah supervisors, madrasah principals, vice principals, and senior teachers. The research results show that: (1) The context of the supervisors' supervision program has provided guidance and coaching to madrasah principals in preparing programs and managing the madrasah; (2) The program inputs include supervisory oversight, limited number of supervisors, facilities and infrastructure, as well as information technology support, which become the main obstacles, in addition to human resources whose capacity still needs improvement; (3) The process of supervision has covered management functions such as planning, implementation, monitoring, and evaluation, although the frequency of supervision is still low and follow-up on supervision results has not been optimal; (4) As for the product, the supervisors' supervision program has made a positive contribution to improving the managerial competence of madrasah principals, although the results achieved are not yet optimal and improvements in the implementation of supervision as well as collaboration among stakeholders are still needed. Thus, it can be concluded that the evaluation of the supervisors' supervision program can improve the quality of the performance of madrasah principals. Therefore, it is recommended that, in order to enhance the performance quality of madrasah principals, the evaluation of the supervisors’ supervision program in madrasahs should be strengthened.Keywords: Supervisory Supervision Program Evaluation, Madrasah Principal Performance. Abstrak: Program supervisi untuk mengawasi kinerja kepala madrasah masih tampak menantang; program tersebut belum sepenuhnya terstruktur, berkelanjutan, atau selaras dengan pemangku kepentingan. Tujuan penelitian ini adalah untuk mengevaluasi program supervisi pengawas dalam meningkatkan kualitas kinerja kepala madrasah di MTsN 2 Bengkulu Selatan. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan model evaluasi CIPP (Konteks, Masukan, Proses, Produk). Subjek penelitian meliputi pengawas madrasah, kepala madrasah, wakil kepala madrasah, dan guru senior. Hasil penelitian menunjukkan bahwa: (1) Konteks program supervisi pengawas telah memberikan bimbingan dan pelatihan kepada kepala madrasah dalam mempersiapkan program dan mengelola madrasah; (2) Masukan program meliputi supervisi pengawas, jumlah pengawas yang terbatas, fasilitas dan infrastruktur, serta dukungan teknologi informasi, yang menjadi kendala utama, selain sumber daya manusia yang kapasitasnya masih perlu ditingkatkan; (3) Proses supervisi telah mencakup fungsi manajemen seperti perencanaan, pelaksanaan, pemantauan, dan evaluasi, meskipun frekuensi supervisi masih rendah dan tindak lanjut terhadap hasil supervisi belum optimal; (4) Adapun produknya, program supervisi pengawas telah memberikan kontribusi positif dalam meningkatkan kompetensi manajerial kepala madrasah, meskipun hasil yang dicapai belum optimal dan perbaikan dalam pelaksanaan supervisi serta kolaborasi antar pemangku kepentingan masih diperlukan. Dengan demikian, dapat disimpulkan bahwa evaluasi program supervisi pengawas dapat meningkatkan kualitas kinerja kepala madrasah. Oleh karena itu, disarankan agar, untuk meningkatkan kualitas kinerja kepala madrasah, evaluasi program supervisi pengawas di madrasah harus diperkuat.Kata kunci: Evaluasi Program Supervisi Pengawas, Kinerja Kepala Madrasah.